METHOD OF ADMINISTRATIVE-TERRITORIAL ZONING OF THE DESIGN PARAMETERS OF AIR TEMPERATURE (Advances in Civil and Architectural Engineering, 2021)
This study proposes a method of administrative-territorial zoning of the major design parameters of the air temperature. For each administrative region, the design values of the mean temperature of the year, the temperatures in the coldest and the warmest month, and the temperature of the coldest and the warmest day are set. These parameters can be applied during the building and in the structural design of the entire region. The study was conducted in Ukraine, however, is applicable to all countries.